Operational Inefficiencies, Bottlenecks, and Poor Layout in Post-Harvest Processes as Barriers to Agro-Industry Productivity and Profitability: A Systematic Literature Review and Case Study - Kurniawan, Rudi; usmiyatun, usmiyatun; Sulistyowati, Enik; Ardianik, Ardianik (Assyfa Journal Scientific Essay, 2025)
Serious challenges in the agro-industry—such as operational inefficiencies, process bottlenecks, and suboptimal post-harvest facility layouts—directly reduce productivity, product quality, and profitability. While numerous studies have examined agricultural process improvements, a significant empirical gap exists between 2022 and 2026 regarding the comprehensive integration of industrial techniques—particularly Lean Manufacturing, Six Sigma, and Discrete-Event Simulation (DES)—in the context of sustainable food systems. This study aims to identify post-harvest operational problem patterns and the most effective optimization approaches through a PRISMA-based Systematic Literature Review (SLR) and a cross-case study synthesis. Secondary data were collected from publications in Scopus, Web of Science, and Google Scholar from 2022–2026, with analysis including waste mapping, bottleneck evaluation, layout analysis, and process simulation. The SLR results (n=38 articles) indicate that key post-harvest bottlenecks include excessive cycle times, process queues, overhandling, non-linear layouts, and low digital integration. Case studies show that the combination of Lean–Six Sigma–DES can reduce lead time by 15–45%, reduce waste by 20–60%, increase OEE (Overall Equipment Effectiveness) by up to 18%, and increase profitability by 12–30%. This research confirms the significant contribution of industrial engineering in realizing a sustainable agricultural system, increasing supply chain efficiency, and optimizing the added value of the agro-industry, becoming a reference for MSMEs, farmers, and policymakers